2000
DOI: 10.1034/j.1399-0039.2000.550603.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor correspondence between predicted and experimental binding of peptides to class I MHC molecules

Abstract: Naturally processed peptides presented by class I major histocompatibility complex (MHC) molecules display a characteristic allele specific motif of two or more essential amino acid side chains, the so-called peptide anchor residues, in the context of an 8-10 amino acid long peptide. Knowledge of the peptide binding motif of individual class I MHC molecules permits the selection of potential peptide antigens from proteins of infectious organisms that could induce protective T-cell-mediated immunity. Several me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 43 publications
1
47
0
2
Order By: Relevance
“…3 In the present study, the amino-acid sequence of the Mcl-1 protein was screened for the most probable HLA-A1 nona-and decamer peptide epitopes, using the main HLA-A1-specific anchor residues. 4 peptides only bound HLA-A1 very weakly. Subsequently, we scrutinized PBL from HLA-A1 þ cancer patients of different origins by means of ELISPOT against the Mcl-1(177-185) peptide as described.…”
Section: To the Editormentioning
confidence: 91%
See 1 more Smart Citation
“…3 In the present study, the amino-acid sequence of the Mcl-1 protein was screened for the most probable HLA-A1 nona-and decamer peptide epitopes, using the main HLA-A1-specific anchor residues. 4 peptides only bound HLA-A1 very weakly. Subsequently, we scrutinized PBL from HLA-A1 þ cancer patients of different origins by means of ELISPOT against the Mcl-1(177-185) peptide as described.…”
Section: To the Editormentioning
confidence: 91%
“…Omi/HtrA2, a serine protease that also reside in intermembrane mitochondrial space, can act in both ways. 4 Recently, Okada and co-workers 5 observed that serine protease inhibitors TLCK and TPCK prevented the z-VAD-fmk plus imatinib-induced necrosis-like programmed cell death (PCD) pathway. They further found that serine protease inhibitors alone failed to prevent imatinib-treated cells from death.…”
Section: To the Editormentioning
confidence: 99%
“…The amino acid sequence of the survivin protein was screened for the most probable HLA-A2 11-mer peptide epitopes, using the main HLA-A2 specific anchor residues. 32 Six survivin deduced peptides were synthesized and examined for binding to HLA-A2. None of the peptides examined bound with similar high affinity as a known positive control epitope from Epstein-Barr virus BMLF280-288 peptide (GLCTLVAML) ( Table 4).…”
Section: Identification Of a Novel Hla-a2 Restricted Survivin Epitopementioning
confidence: 99%
“…9 ) and scrutinized PBL from HLA-A3 þ cancer patients of different origin for reactivity against these peptides, taking advantage of the ELISPOT assay. This method has previously been shown to be highly efficient for the identification of tumor-specific CTL in cancer patients.…”
Section: To the Editormentioning
confidence: 99%